Pengaruh Model Pembelajaran Two Stay Two Stray Terhadap Hasil Belajar Siswa pada Mata Pelajaran Administrasi Umum di SMK Ketintang Surabaya - Adisty Dwi Putri; Durinda Puspasari (Universitas Negeri Surabaya, 2020)
Researchers have a goal in research that is to determine the application of the two stay two stray learning model on student learning outcomes in general administration subjects at SMK Ketintang Surabaya and to determine the effect of the two stay two stray learning model on student learning outcomes in general administration subjects in SMK Ketintang Surabaya. This study uses an experimental research type with an experimental design quaisi in the form of nonequivalent group pretest posttest design. The population in this study used class X OTKP 1, OTKP 2, and OTKP 3 with a total number of 95 students and the sample used was class X OTKP 2 with a total of 30 students as a control class and class X OTKP 3 with a total of 30 students as an experimental class. This study uses data collection techniques such as observation, interviews, tests, and documentation. The data analysis technique uses validity test, reliability test, difficulty level test, differentiation test, homogeneity test, normality test, t test and gaincore. The results of this study showed the average pretest score in the control class was 55, while the experimental class was 58.12. Then the average posttest in the control class was 70.33, while the experimental class was 83.17. Based on the of the t-test result about the posttest score that has been done by researchers that counted 5.693 with a significance level of 0.000. While the ttable can be searched using the ttable distribution with a confidence level of 95% (Î± = 5%, because the t test is two-sided) with a degree of df 58, so it is known that the ttable is 2.001. Then it can be concluded that tcount (5,693)> ttable (2,001). So it can be concluded that Ha is accepted or there is an influence of two-stay-two-stray learning model on student learning outcomes in general administration subjects at SMK Ketintang Surabaya.